Enhancing the FIRM'S green performance through green HRM: The moderating role of green innovation culture. (20th March 2021) - Muisyo, Paul Kivinda; Qin, Su
Abstract: Prior scholarships have documented that green human resource management practices have performance enabling effects on a firm's green performance. However, there is a dearth of studies that empirically model the extent to which green innovation culture moderates the relationship between green human resource practices and the firm's green performance. To address this gap, this paper established two-fold objectives. First, to examine the effects of green human resource practices and green innovation culture on firm green performance. Second, to model the extent to which green innovation culture moderates the relationship between green human resource management and manufacturing firms' green performance in China. This was done using data obtained from an extensive scale survey of 300 employees in Chinese manufacturing firms located in the Jiangsu Province. The study suggests that green human resource management practices which include recruitment and selection, training and development, performance management and appraisal, reward and payment, and employee involvement and leadership have a significant effect on green or environmental performance. The study also suggests that green innovation which includes green product innovation culture and green process innovation culture enhances firm green performance. Our paper further suggests that firms that integrate green human resource management practices and green innovation culture are associated with higher green performance than firms that practice green human resource management only.